O-034 Thrombectomy for acute ischemic stroke in nonagenarians compared to octogenarians. (22nd July 2019) - Sussman, E; Martin, B; Mlynash, M; Marks, M; Marcellus, D; Albers, G; Lansberg, M; Dodd, R; Do, H; Heit, J
Abstract : Introduction: Recent landmark randomized clinical trials have demonstrated that endovascular thrombectomy (EVT) leads to improved outcomes in patients with acute ischemic stroke (AIS) due to large vessel occlusion (LVO). Although elderly patients were excluded from several of these initial trials, the available data suggests a benefit of EVT in octogenarian patients with AIS due to LVO. However, the efficacy of EVT in the nonagenarian patient population remains uncertain. Methods: We performed a retrospective cohort study of a prospectively-maintained stroke database at a single comprehensive stroke center. Inclusion criteria were: age 80–99 years, LVO, core infarct <70mL on perfusion imaging, and presence of a salvageable penumbra. Patients were stratified based on age into octogenarian (age 80–89) and nonagenarian (age 90–99) cohorts. Primary outcome was ordinal score on the modified Rankin Scale (mRS) at 90 days. Secondary outcomes included dichotomized functional outcome (mRS≤2 versus mRS≥3), successful revascularization, symptomatic reperfusion hemorrhage and mortality. Results: 108 patients met inclusion criteria, including 79 octogenarians (73%) and 29 nonagenarians (27%). Mean octogenarian age was 84.2 years (SD 2.8) versus 92 years (SD 2.3) in nonagenarians. Nonagenarians were more likely to be female (86% versus 58%; p<0.01); there were no other differences between the groups in terms of demographics, medical comorbidities, pre-treatment clinical variables, or endovascular treatment characteristics. Median mRS at 90 days was 5 (IQR 3–6) in octogenarians and 6 (IQR 4–6) in nonagenarians (p=0.09). Independent functional status (mRS≤2) at 90 days was achieved in 13% of nonagenarians and in 20% of octogenarians (p=0.54). Successful revascularization (TICI 2b-3) was achieved in 79% in both the octogenarian and nonagenarian cohorts (p=1). Symptomatic reperfusion hemorrhage occurred in 21% of nonagenarians and in 6% of octogenarians (p=0.03). The 90-day mortality rate was 63% in nonagenarians versus 41% in octogenarians (p=0.07). Conclusions: Nonagenarian patients undergoing EVT for AIS due to LVO are at significantly higher risk of symptomatic reperfusion hemorrhage compared with octogenarians, despite similar stroke- and treatment-related factors. While there was a strong trend towards higher mortality rates and worse long-term functional outcomes in nonagenarians, the difference was not statistically significant in this relatively small retrospective study. Additional prospective and randomized studies are necessary to evaluate the efficacy of EVT in elderly patients, including nonagenarians. Disclosures: E. Sussman: None. B. Martin: None. M. Mlynash: None. M. Marks: None. D. Marcellus: None. G. Albers: None. M. Lansberg: None. R. Dodd: None. H. Do: None. J. Heit: None.